2020
DOI: 10.3390/diagnostics10100839
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Accuracy of Biomarkers for Early-Onset Neonatal Bacterial Infections: Evaluation of Serum Procalcitonin Reference Curves

Abstract: To date, no clinical studies have compared the accuracy of serum procalcitonin (PCT) reference curves. We aimed to validate the diagnostic accuracy of previously reported serum PCT reference curves and to determine which biomarkers among a cut-off value over the 95th percentile in the serum PCT reference curve, white blood cell (WBC) count, and C-reactive protein (CRP) and immunoglobulin M (IgM) levels, have the highest diagnostic accuracy for early-onset neonatal bacterial infections. This retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Previously, the clinical diagnosis of neonatal infectious diseases was based on the detection of peripheral blood WBC counts, and the results of WBC detection were affected by various factors, and some neonates had poor WBC count bases, and the detected WBC levels were still in the normal range even though bacterial infections had occurred in the body, so WBC could only be used as a routine reference index for the diagnosis of infectious diseases ( 21 , 22 ). CRP, synthesized by inflammatory factors stimulating hepatocytes, is an acute phase response protein that triggers immunomodulation, phagocytosis, formation of immune complexes, and activation of the complement system, and has been clinically used as a nonspecific marker of the systemic inflammatory response ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the clinical diagnosis of neonatal infectious diseases was based on the detection of peripheral blood WBC counts, and the results of WBC detection were affected by various factors, and some neonates had poor WBC count bases, and the detected WBC levels were still in the normal range even though bacterial infections had occurred in the body, so WBC could only be used as a routine reference index for the diagnosis of infectious diseases ( 21 , 22 ). CRP, synthesized by inflammatory factors stimulating hepatocytes, is an acute phase response protein that triggers immunomodulation, phagocytosis, formation of immune complexes, and activation of the complement system, and has been clinically used as a nonspecific marker of the systemic inflammatory response ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of D-D: 1 Take the clever kit from the cold storage, equilibrate at room temperature for at least half an hour, add 1.1 mL of D-D gold standard lyophilized product to the lyophilized product of D-D gold standard solution and shake it well; 2 Lay the D-D reaction plate flat on the laboratory bench, and add 2 drops of D-D blocking solution to the reaction hole to make it completely infiltrate; 3 Use a sterile tip to absorb 100ul organic acid Add anticoagulant plasma to the reaction plate. After it is completely infiltrated, add 2 drops of D-D washing solution; 4 When the washing liquid is completely infiltrated, use a clean tip to accurately add 100ul of D-D colloidal gold solution; 5 After the infiltration is complete, add 4 drops of D-D washing solution; 6 Immediately read the absorbance (OD value) under the D-D item of the U2 gold standard quantifier, and calculate the D-D concentration in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…More and more studies have shown that PCT levels in the blood of patients with bacterial infections will increase, especially in patients with severe bacterial infections or sepsis. 6 , 7 Therefore, in foreign clinical practice, PCT is often regarded as one of the sensitive indicators for the diagnosis of severe sepsis and is used in clinical diagnosis, treatment, and prognosis. The chelation of Fe 3+ with serum transferrin can transport free iron ions.…”
Section: Introductionmentioning
confidence: 99%
“…8 Accuracy of serum PCT reference curves of serum PCT levels for neonates has recently been evaluated. 9 The serum PCT reference curves published by Fukuzumi et al were found to have the highest diagnostic accuracy. 10 For preterm infants, the PCT level alone with a cutoff value more than the 95th percentile in the serum PCT reference curve, and for term infants, the PCT level, and CRP level in combination with WBC count and/or IgM level should be used for the detection of early-onset bacterial infection.…”
Section: Serum Pctmentioning
confidence: 97%